Pengaruh Motivasi Berwirausaha, Pengetahuan Kewirausahaan Dan Lingkungan Keluarga Terhadap Minat Berwirausaha (Studi Kasus Pada Mahasiswa Manajemen FEB UNISMA Angkatan 2020) - Fa’iqoh, Fina Hilyah; Hidayati, Nur; Arsyianto, Muhammad Tody (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aims to determine and analyze the effect of entrepreneurial motivation, entrepreneurial knowledge, and family environment on entrepreneurial interest. case study on management students of the Faculty of Economics and Business, Islamic University of Malang class of 2020. The number of samples collected was 83 respondents. This research method uses multiple linear regression analysis using the SPSS program. The results of this study are entrepreneurial motivation, entrepreneurial knowledge, and family environment simultaneously affect the interest in entrepreneurship. Partially variable entrepreneurial motivation and entrepreneurial knowledge has a significant effect on the interest in entrepreneurship while the family environment variable has no significant effect on the interest in entrepreneurship.  Keywords : Entrepreneurial Motivation, Entrepreneurial Knowledge, Family Environment, Entrepreneurial Interest